2021
DOI: 10.3762/bjnano.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of vibration modes of a qPlus sensor with a long tip

Abstract: We study the oscillatory behavior of qPlus sensors with a long tilted tip by means of finite element simulations. The vibration modes of a qPlus sensor with a long tip are quite different from those of a cantilever with a short tip. Flexural vibration of the tungsten tip will occur. The tip can no longer be considered as a rigid body that moves with the prong of the tuning fork. Instead, it oscillates both horizontally and vertically. The vibration characteristics of qPlus sensors with different tip sizes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…They revealed the lateral tip oscillation in the second mode and demonstrated topographic imaging with the sensor. Afterward, Chen et al also reported a FEM study on the QTF sensors with an angled-attached long probe with various probe lengths and diameters 30 . In contrast, we found the lateral tip oscillation in the higher flexural mode of a qPlus sensor where a long probe was attached perpendicularly to the QTF prong (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…They revealed the lateral tip oscillation in the second mode and demonstrated topographic imaging with the sensor. Afterward, Chen et al also reported a FEM study on the QTF sensors with an angled-attached long probe with various probe lengths and diameters 30 . In contrast, we found the lateral tip oscillation in the higher flexural mode of a qPlus sensor where a long probe was attached perpendicularly to the QTF prong (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…First, the determination of the spring constant and oscillation amplitude is necessary for the quantitative analysis of tip-sample interaction. The effective spring constant of the qPlus sensor with a long probe was already analyzed by FEM 28,30,31 . Some methods to calibrate the amplitude of the higher mode of the qPlus sensor with a long probe were proposed, such as scanning electron microscopy 28,30 and laser Doppler vibrometry 31,32 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations